Prinsip Buddha Zen dalam Upacara Chanoyu Aliran Urasenke - Widya Magdalena (Japanese Research on Linguistics, Literature, and Culture, 2019)
This research discusses about the application of the Zen Buddhism principles in urasenke style tea ceremony. The purpose of this research is to explain the application of the Zen principles (wa, kei, sei, jaku) in urasenke style tea ceremony. This research used descriptive qualitative method to analyze the data. This study uses the principles given by Sen no Rikyu. These principles are wa (harmony), kei (respect), sei (purity), and jaku (tranquility). The results of this study show that the four principles are applied through the actions taken by the host and guest in the urasenke style tea ceremony. Keywords         : chanoyu, urasenke, buddhism, zen, Japan